Comradely objects Design and material culture in Soviet Russia, 1960s-80s - Karpova, Yulia (Manchester University Press, 2020)
The major part of this book project was funded by the European Union's Horizon 2020 research and innovation programme under the Marie Sklodowska-Curie grant agreement No. 700913. This book is about two distinct but related professional cultures in late Soviet Russia that were concerned with material objects: industrial design and decorative art. The Russian avant-garde of the 1920s is broadly recognised to have been Russia's first truly original contribution to world culture. In contrast, Soviet design of the post-war period is often dismissed as hackwork and plagiarism that resulted in a shabby world of commodities. This book identifies the second historical attempt at creating a powerful alternative to capitalist commodities in the Cold War era. It offers a new perspective on the history of Soviet material culture by focusing on the notion of the 'comradely object' as an agent of progressive social relations that state-sponsored Soviet design inherited from the avant-garde. It introduces a shared history of domestic objects, handmade as well as machine-made, mass-produced as well as unique, utilitarian as well as challenging the conventional notion of utility. Situated at the intersection of intellectual history, social history and material culture studies, this book elucidates the complexities and contradictions of Soviet design that echoed international tendencies of the late twentieth century. The book is addressed to design historians, art historians, scholars of material culture, historians of Russia and the USSR, as well as museum and gallery curators, artists and designers, and the broader public interested in modern aesthetics, art and design, and/or the legacy of socialist regimes.